Mindfulness and work addiction among young employees: the mediating roles of cognitive reappraisal and perfectionism - Gao Zheng; Jiafan Sheng; Huilin Wang; Ziqing Xu (Frontiers in Psychiatry)
IntroductionWork addiction has become a growing concern among young employees in China, fueled by an “always-on” work culture that has been amplified by the rise of digital technologies. This study investigates the psychological mechanisms that contribute to work addiction, focusing on mindfulness, cognitive reappraisal, and perfectionism. Understanding these mechanisms is crucial for developing effective strategies to combat work addiction, particularly in the context of the increasingly digital and competitive work environment in China.MethodsAn online survey was administered to 362 young employees in southern China using convenience and snowball sampling methods. Data was analyzed using structural equation modeling (SEM) with the software SmartPLS 4 to examine the relationships between mindfulness, cognitive reappraisal, perfectionism, and work addiction. Mediation analysis was conducted to test the indirect effects of cognitive reappraisal and perfectionism on the relationship between mindfulness and work addiction.ResultsThe results revealed that mindfulness was positively associated with cognitive reappraisal and negatively correlated with perfectionism. Cognitive reappraisal was found to be negatively related to work addiction, while perfectionism showed a positive relationship with work addiction. Mediation analysis confirmed that both cognitive reappraisal and perfectionism mediated the relationship between mindfulness and work addiction.DiscussionThis study highlights the role of mindfulness as a key factor in reducing work addiction among young employees. By enhancing cognitive reappraisal and reducing perfectionism, mindfulness can effectively mitigate the psychological drivers of work addiction. The findings suggest that organizations can implement mindfulness-based interventions to improve emotional regulation and work-life balance among young employees, ultimately helping to reduce work addiction and its associated negative impacts. The study also underscores the importance of conducting research in diverse cultural settings to further understand the global relevance of these psychological mechanisms.